Strengthening the Early Detection Capability of CBRN Crimes to Improve National Security: Memperkuat Kemampuan Deteksi Dini Kejahatan CBRN untuk Meningkatkan Keamanan Nasional - Albertus Digwijaya Anindyajati; Susilastuti Susilastuti; Ikhlas Nur Muhammad (Universitas Negeri Semarang, 2024)
The threat of Chemical, Biological, Radiological and Nuclear (CBRN) crimes is increasingly complex and has the potential to disrupt the stability of Indonesia's domestic security. This study aims to analyse efforts to strengthen early detection capabilities against CBRN crimes to improve national security. The method used is a qualitative approach with descriptive-analytical method, supported by literature study and SWOT analysis. The results show that although Indonesia has supporting institutions and regulations, such as BAPETEN, BRIN, as well as Law No. 10 of 1997 and Presidential Instruction No. 4 of 2019, cross-sector coordination is still weak and there is no leading sector that regulates the handling of CBRN threats in an integrated manner. Several real cases such as the use of radioactive materials by terrorist groups in Bandung 2017 and the delivery of envelopes containing anthrax in Jakarta 2019 emphasise the urgency of strengthening the early detection system. The SWOT analysis recommends policy priorities in the form of establishing a national coordinating institution, increasing human resource capacity and detection technology, developing integrated protocols, and strengthening international cooperation. With strategic and collaborative steps, Indonesia can build a CBRN early detection system that is resilient and responsive in facing future threat dynamics.